Multi-high valence state metal doping in NiFe hydroxide toward superior oxygen evolution reaction activity. Issue 6 (24th January 2023) - Sari, Fitri Nur Indah; Frenel, Gally; Lee, Alex Chinghuan; Huang, Yan-Jia; Su, Yen-Hsun; Ting, Jyh-Ming
Abstract : FeNiVTiCr hydroxide, fabricated through a facile Ni-corrosion method at room temperature, is demonstrated to be an outstanding OER electrocatalyst, outperforming commercial electrocatalysts. Abstract : In this study, we demonstrate multi-high valence 3d transition metal (TM) doping to boost the oxygen evolution reaction (OER) activity and stability of NiFe hydroxide. Self-supported NiFe hydroxides with multiple high valence 3d TM (V 4+, V 5+, Ti 3+, Ti 4+, Co 3+, and Cr 3+ ) doping are fabricated using a facile Ni-corrosion method at room temperature without the use of any additional oxidizing agent. The high-valence metal dopants effectively tune the electronic structure of Ni. In situ Raman, ex situ electron energy-loss spectroscopy, and density functional theory calculations reveal that Cr is advantageous for the formation of oxyhydroxide with the longest Ni–O bond length, facilitating the decomposition of *OOH intermediate species for the generation of O2 . Additionally, Ti contributes to charge transfer. The optimized NiFe hydroxide with V, Ti, and Cr dopants (FNVTiCr) outperforms the benchmark RuO2 and reported Ni-based catalyst by exhibiting an overpotential of 240 mV at 100 mA cm −2 and stability for 70 h. Notably, an alkaline electrolyzer with an FNVTiCr anode and Pt/C cathode is also demonstrated with an ultralow cell voltage of 1.49 V to generate a current density of 10 mA cm −2, which is stable for 100 h, surpassing the benchmark industrial catalyst. This multi-high valence 3d TM doping approach provides a strategy for designing a low-cost, effective, and stable Ni-based catalyst.